Studi Karakteristik Pohon Bertengger Celepuk Rinjani (Otus jolandae) di Desa Wisata Jeruk Manis, Lombok Timur, Nusa Tenggara Barat - Jupri, Ahmad; Isrowati, Isrowati; Sukraeni, Komang Ratna Aprilia; Khazimi, Ahmad Sadam; Alda, Tri Rahmi Fitri; Hidayati, Lilik (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
The study entitled Characteristics of Food Tree Habitat and Langur Population in Jeruk Manis Tourism, Kembang Kuning Resort, TNGR aims to understand the role of habitat in the survival of the Javan langur (Trachypithecus auratus), an endangered primate species. The Javan langur functions as a natural seed disperser in the forest, and its presence is very important for the plant regeneration process. This study was conducted in November-December 2024 in Kembang Kuning Village, East Lombok, using the population census method and vegetation analysis. The research method includes collecting data on the langur population through the concentration method and vegetation analysis by creating sample plots measuring 20 x 20 m. The results showed that the langur population varied in various plots, with a higher proportion of adult individuals in some locations, indicating group stability. The data also showed that the bajur tree (Pterocarpus indicus) was the main food source with a high Importance Value Index (INP) value. This study provides insight into the composition and structure of vegetation in the langur habitat, as well as the importance of conserving this species in the face of threats from hunting and habitat loss. By understanding the characteristics of the habitat and distribution patterns of the langur population